2009
DOI: 10.1002/esp.1898
|View full text |Cite
|
Sign up to set email alerts
|

Physical explanations of variations in river meander migration rates from model comparison

Abstract: In meandering rivers, the local channel migration rate increases with increasing bend sharpness until it reaches a maximum at a certain critical value of the bend sharpness. Beyond this critical value, the migration rate decreases if bend sharpness increases. Similarly, reach-averaged migration rates attain a maximum at a certain river sinuosity. This work investigates the physics of these phenomena by comparing the results of two physics-based models of different complexity, in which the migration rates are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 20 publications
3
52
0
Order By: Relevance
“…Previous research has indicated that complex flow patterns around meander bends drastically modify the expected shear stress distribution from the assumption of steady, uniform flow (Papanicolaou et al, 2007;Pizzuto, 2008). Using Crosato's (2007) "no-lag kinematic model" predicted an increased boundary shear stress (up to 2.5 times at peak flow) but resulted in no additional bank retreat than the same simulation with the excess shear stress equation. More sophisticated formulations can be used to increase the boundary shear stress, as it was hypothesized that applied shear stresses are still under predicted, but this is again dependent on data to represent this process.…”
Section: Modeling Bank Retreatmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous research has indicated that complex flow patterns around meander bends drastically modify the expected shear stress distribution from the assumption of steady, uniform flow (Papanicolaou et al, 2007;Pizzuto, 2008). Using Crosato's (2007) "no-lag kinematic model" predicted an increased boundary shear stress (up to 2.5 times at peak flow) but resulted in no additional bank retreat than the same simulation with the excess shear stress equation. More sophisticated formulations can be used to increase the boundary shear stress, as it was hypothesized that applied shear stresses are still under predicted, but this is again dependent on data to represent this process.…”
Section: Modeling Bank Retreatmentioning
confidence: 89%
“…Papanicolaou et al (2007) suggested that due to secondary currents the bottom half of the streambank may experience stress distributions two to three times higher than the shear stress calculated by first order approximations. In BSTEM, the boundary shear stress is corrected for the effects of curvature using the "no-lag kinematic model" (Crosato, 2007):…”
Section: Introductionmentioning
confidence: 99%
“…Shear stress is typically greater in the outside of meander bends due to higher maximum velocities near the bank, super-elevation of the water surface, and secondary currents directed towards the bank (Knighton, 1998). BSTEM accounts for these effects by adjusting the average boundary shear stress (Crosato, 2009(Crosato, , 2007:…”
Section: A1 Bstem Summarymentioning
confidence: 99%
“…The mathematical model adopted in this study, Miandras (Crosato, 1987(Crosato, , 2008(Crosato, , 2009, computes the longitudinal profiles of the nearbank excesses of flow velocity and water depth, U and H, respectively, with respect to the reach-averaged values, u 0 and h 0 ( Figure 3). These excesses are caused by the local channel curvature and by upstream geometrical discontinuities such as a change of channel curvature (bend entrance and exit), which, under certain conditions lead to the formation of steady alternate bars in the river channel (Struiksma et al, 1985).…”
Section: Channel Migration Modelmentioning
confidence: 99%
“…A full model description is given by Crosato (1987Crosato ( , 2007Crosato ( , 2008Crosato ( , 2009). …”
Section: Water Managementmentioning
confidence: 99%